Dragon fruit-kiwi fermented beverage: In vitro digestion, untargeted metabolome analysis and anti-aging activity in Caenorhabditis elegans - Tang, Zizhong; Zhao, Zhiqiao; Chen, Siyi; Lin, Wenjie; Wang, Qing; Shen, Nayu; Qin, Yihan; Xiao, Yirong; Chen, Hong; Chen, Hui; Bu, Tongliang; Li, Qingfeng; et al. (Frontiers in Nutrition, 2023)
The research on the development of dragon fruit and kiwi fruit through lactic acid-yeast compound fermentation is very limited, and there are few related fermentation products on the market. The purpose of this study was to evaluate the stability of the antioxidant capacity of fermented beverages (FB) through in vitro simulated digestion, to evaluate the changes in metabolites of juice after fermentation through untargeted metabolomics, and used Caenorhabditis elegans as a model to evaluate its anti-aging activity. The results showed that FB not only has good in vitro antioxidant activity, but also the total phenol content (TPC), total flavonoid content (TFC), ABTS scavenging ability, and hydroxyl radical scavenging ability of FB were significantly increased during gastric digestion and intestinal digestion. Metabolomics showed that the contents of phenols and flavonoids related to antioxidant increased after fermentation, and fermentation had a significant effect on organic acids and amino acids in FB. Finally, compared with the control group, the mean lifespan of C. elegans fed with 1.56% FB increased by 18.01%, SOD activity significantly increased by 96.16% and MDA content significantly decreased by 40.62%. FB has good antioxidant activity in vitro and in vivo, and the antioxidant activity is stable during the simulated digestion process.